Resistance welding of coated steel plates in the aspect of environmental conditions - Matusiak, J.; Wycislik, J. (Автоматическая сварка, 2016)
In the industry, resistance welding has always been regarded as the process without significant adverse effect on the work environment. The research literature of the last years dealing with investigations into fume and chemical factors of resistance welding was the only reason that has directed the attention of specialists on working safety to the amount and type of pollutants emitted during this process. The article presents research conducted at Instytut Spawalnictwa in Gliwice, into the emission of pollutants generated during spot resistance welding of steel plates with various protective coatings. The article demonstrates the research station and methodology of determination of total fume, carbon monoxide, nitrogen oxides and organic matters. The examination of fume and gas emission was conducted during resistance welding of electrolytic and hot-dip coated plates, covered with zinc, zinc and iron alloy, aluminium with the admixture of silicon as well as zinc-epoxy double layer coatings. The comparative analysis of the research results was aimed at the determining the impact of coating type and welding current on emission of fumes and gases during resistance welding of plates with different thickness.